(untitled) - Erickson, John R.; 1943-; Holmes, Gerald L. (New York, 2001)
Hank the Cowdog, Head of Ranch Security, and assistant deputy Drover engage in an epic battle with the coyotes, Rip and Snort, as they all seek some meaty treats.
Keywords: Humorous Stories; Mystery and detective stories; Fiction; Ranch life; West (U.S.); Coyote; Fiction; Dogs; Fiction; West (U.S.); Fiction